Working for a Better Life: Longitudinal Evidence on the Predictors of Employment Among Recently Arrived Refugee Migrant Men Living in Australia. (8th May 2013) - Correa‐Velez, Ignacio; Barnett, Adrian G.; Gifford, Sandra
Abstract Although a number of studies have investigated the predictors of employment among refugee migrants, there is a dearth of evidence from longitudinal data. This study investigated the cross‐sectional and longitudinal predictors of employment among 233 adult refugee men living in South‐East Queensland, Australia. Participants were interviewed four times at six‐month intervals between 2008 and 2010. Using a conceptual model developed from the literature, Generalized Estimating Equations were used to model the predictors of employment. Over time, the employment rate increased from 44 per cent to 56 per cent. Region of birth, length of time in Australia, seeking employment through job service providers and informal networks, and owning a car were significant predictors of employment. Contrary to previous research, English language proficiency was not a significant predictor when other variables were controlled for. Recognition of overseas skills and qualifications decreased the chances of finding employment. The policy and programme implications are discussed. <boxed-text content-type="box" id="imig12099-blkfxd-0001" position="anchor" orientation="portrait"> Policy Implications Recognition of refugee migrants' overseas‐gained skills and qualifications does not guarantee them securing employment. Recognition of overseas skills and qualifications should be accompanied by educating employers, especially those outside the traditional migrant employment 'niches', about the resources and capabilities of refugee migrants, and the value of their qualifications. Fostering programmes that target the needs of job seekers from refugee backgrounds could enhance their employment outcomes. Supporting refugee migrants getting their drivers' licence and establishing favourable loan programmes that enable refugee migrants to buy a car can have a positive impact on their workforce participation. </boxed-text>